Pre-employment honesty testing in Croatia: Development and Initial Validation of Personality-, Attitude-, and Admission-Based Integrity Tests - Tonković Grabovac, Maša (2012)
Workplace thefts result in huge economical losses for organizations and government. Hence, integrity tests would be especially useful for Croatian economy, where workplace thefts and other CWB are relatively frequent behavior. However, both Croatian selection research and practice lack such an instrument. Given the potential cultural specificity of the concept of workplace integrity, the goal of this study was to develop and validate the Croatian Integrity Test. The sample consisted of 277 Croatian students, which anonymously filled in the three integrity scales of Croatian Integrity Test (CIT, Tonković & Jerneić, 2012): Personality- , Attitude- and Admission-based. The scales were modeled after existing honesty tests and after thorough theoretical examination of constructs of integrity and counterproductive work behavior . All the three scales of the Croatian Integrity Test (Personality-, Attitude-, and Admission-based ) showed satisfactory psychometrical characteristics. Based on their inter-correlations and correlations with other measures of integrity and related constructs, we concluded they could be regarded as promising instruments for measuring integrity in research and practice of personnel selection in Croatia.
ENG